FUNDAMENTALISATION OF ECONOMIC EDUCATION: FOREIGN EXPERIENCE IN FORMATION OF ENTREPRENEURIAL SKILLS - Ножовнік, О. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article is dedicated to pedagogical analysis of foreign experience in forming entrepreneurial skills in the students of higher economic institutions given the opportunity to implement its elements into the process of fundamentalisation of national higher economic education. The article draws attention to the most effective educational systems, offering economic vocational training, such as Austria, Germany, France, Italy, Great Britain, Scandinavia, and certainly the United States and Canada. At the same time, it has been noted that an interesting and revealing in the context of preserving national mentality and time-honoured cultural traditions of vocational education is the East region countries – Japan, China and Vietnam. Having based on the empirical research data, there has been found that modern European higher education is gradually being transformed into an educational model in which all relevant tasks and educational components are integrated into the «knowledge triangle» with elements of «education – research – innovation», at the same time the East region countries, adapting the leading European and American models of both higher education in general and business education in particular, take into account time-honoured social traditions and show an example of an optimal system of the professional self-development of the future specialist-economist